Envelope shaping technology for power amplifier based on PXI platform - Du Feifan (Journal of Shanghai Normal University (Natural Sciences), 2017)
The difference between Envelope Tracking power amplifier (ETPA) and normal PA is the performance of system which is not only related to the Radio Frequency (RF) input signal,but also related to the envelope signal.In order to deeply analysis the system,based on PXI platform,the synchronization and timing technology,different envelope shaping technologies,including ISO-Gain method will be discussed in the paper,which will lead to different trade-off between gain,linearity and efficiency.And a new correction method for power modulator will be discussed.